IMPLEMENTATION OF TPACK-BASED LEARNING DESIGN ON THE ROTATING OBJECT CONCEPT - Ariyanti, Gregoria; Dian, Mariani; Indrawati, Chatarina Dian (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2024)
This study aims to implement a learning design based on technological pedagogical and content knowledge (TPACK) on the concept of rotating object. The research subjects were students of class XII IPA SMAK Santo Bonaventura Madiun. The data were obtained from observations and student test results in completing the concept of rotating object. This research is a development research. Mathematics is still considered a difficult subject by some students. For elementary and middle school level mathematics, it is still possible to deliver it based on students' experiences in everyday life. For the senior high school level, the concept of rotating object is difficult to imagine because it requires a higher understanding. Therefore, it is necessary to design learning that can provide direct experience to students. TPACK is learning that uses a combined application of an education system that prioritizes technology and certain applications (content) in learning. In implementing TPACK-based learning, there are several things to pay attention to, namely aspects of pedagogy, content, and technology. The findings of this study indicate an increase in student learning outcomes in the rotating object concept